Human evolution - Gardner, Robert, 1929-; DiGeorgio, Mike; Rasch, Patricia (New York : F. Watts, 1999)
Traces past and present theories of human origins and development.
Geology, evolution, and culture -- Darwin's theory evolves -- Human evolution in Europe and Asia -- Human evolution : the evidence from Africa -- The origin, emergence, and spread of modern humans -- Language : a human advantage -- Culture : another human advantage -- A human lineage.
"A Franklin Watts library edition"--Jacket.
Includes glossary.
Includes bibliographical references (p. 134-138) and index.
Books for the Teen Age (NYPL).
Wilson's Junior High School.
Wilson's Senior High School.
Keywords: Human evolution -- Juvenile literature; Evolution; Evolution